2010
DOI: 10.1111/j.1365-2036.2009.04172.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin EP2 receptor expression is increased in Barrett’s oesophagus and oesophageal adenocarcinoma

Abstract: SUMMARY BackgroundAccumulating evidence suggests that cyclooxygenase-2 (COX-2)-derived prostaglandin E2 (PGE2) is involved in oesophageal adenocarcinogenesis. PGE2 exerts its biological action by binding to specific receptors (EP1, EP2, EP3 and EP4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 37 publications
2
52
1
Order By: Relevance
“…Our findings of the EP2 expression in TAFs in the mesenchyme are consistent with our previous finding that EP2 was expressed in stromal region in Apc D716 mice and Ptger2 deficiency suppressed intestinal polyp formation (43). Furthermore, several studies reported expression of EP2 in various types of cancers (44)(45)(46) and aspirin lowers the risk of solid tumors other than colorectal cancer (4,5). It is interesting to test how widely the EP2 actions we found here operate in microenvironment of cancers other than colorectal cancer.…”
Section: Ly-6gsupporting
confidence: 81%
“…Our findings of the EP2 expression in TAFs in the mesenchyme are consistent with our previous finding that EP2 was expressed in stromal region in Apc D716 mice and Ptger2 deficiency suppressed intestinal polyp formation (43). Furthermore, several studies reported expression of EP2 in various types of cancers (44)(45)(46) and aspirin lowers the risk of solid tumors other than colorectal cancer (4,5). It is interesting to test how widely the EP2 actions we found here operate in microenvironment of cancers other than colorectal cancer.…”
Section: Ly-6gsupporting
confidence: 81%
“…In the esophagus, Jiménez et al (11) showed that, in addition to COX-2, EP 2 and EP 4 receptor expression and protein were increased in the Barrett's metaplasia-intraepithelial neoplasiaadenocarcinoma sequence. Among these two PGE 2 receptors, OE33 xenografts showed higher expression for EP 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the involvement of COX-2 in esophageal adenocarcinoma includes epidemiological studies which have demonstrated a protective effect of NSAIDs against esophageal adenocarcinoma (4,5), in vivo studies in experimental models of reflux-induced esophageal adenocarcinoma in rats, where administration of non-steroidal anti-inflammatory drugs (NSAIDs) or selective COX-2 inhibitors (coxibs) induced a reduction of esophageal cancer incidence (6)(7)(8)(9)(10). In addition, up-regulation of COX-2 has been described both at mRNA and protein level along the Barrett's metaplasia-dysplasia-adenocarcinoma sequence in humans (11)(12)(13)(14)(15)(16)(17) and COX-2 expression has been identified as an independent prognostic variable for esophageal adenocarcinoma (18), indicating that COX-2 could be a molecular target for specific chemotherapeutic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas its mechanisms of action have been well elucidated for inflammation, less is known for cancer promotion. Some experimental studies demonstrated that COX-2 over-expression is associated with a significant decrease of apoptosis, an increase in malignant cell invasiveness and an enhancement of prostaglandin synthesis and cell proliferation [22]. Opposite effects together with decreased angiogenesis are associated with COX-2 inhibition [23].…”
Section: Discussionmentioning
confidence: 99%